Bone Turnover Markers in Adults with Nonalcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis - Chao Li; Yali Cui; Wenjie Zhou; Yiduo Zhang; Xiaocui Huang; Fan Yu (International Journal of Endocrinology)
Objective. Previous studies suggested that the level of bone turnover markers (BTMs) could be altered in patients with nonalcoholic fatty liver disease (NAFLD). We aim to provide a comprehensive understanding on the associations between BTMs and NAFLD in adults with a meta-analysis. Methods. Articles published up to January 31, 2023, were systematically searched in PubMed, Web of Science, Cochrane database, Embase, and CNKI. The search formula is as follows: “nonalcoholic fatty liver disease” combined with the terms that bone turnover markers such as “osteocalcin,” “collagen type I trimeric cross-linked peptide,” and “procollagen type I N-terminal peptide.” Stata 15.0 software was used to calculate the pooled OR (95% CI) and perform the heterogeneity test, sensitivity analysis, and publication bias. Results. We identified 18 studies with a total of 12,310 participants. Statistical differences were found between patients with NAFLD compared to the control group for osteocalcin (n = 15 studies; SMD: −0.69; 95% CI: −0.73–−0.64; P=0.002), procollagen type I N-terminal propeptide (n = 5 studies; SMD: −0.40; 95% CI: −0.80−−0.00; P=0.049), and collagen type I cross-linked C-telopeptide (n = 7 studies; SMD: −0.16; 95% CI: −0.23−−0.09); P<0.001). Conclusion. Bone turnover markers were lower in patients with NAFLD compared to the control group.